Insight into tetrahydrofuran lignans from Isatis indigotica fortune with neuroprotective and acetylcholinesterase inhibitor activity. (April 2023) - Xi, Yu-Fei; Bai, Ming; Zhang, Xin; Hou, Zi-Lin; Lin, Bin; Yao, Guo-Dong; Lou, Li-Li; Wang, Xiao-Bo; Song, Shao-Jiang; Huang, Xiao-Xiao
Abstract: Nine tetrahydrofuran lignans, including three undescribed spiro-lignans, were isolated from Isatis indigotica Fortune (Brassicaceae). Extensive spectroscopic analyses achieved the structure elucidation of these tetrahydrofuran lignans, and quantum chemical calculation combined with the MAEΔΔ δ parameter. Notably, isatispironeols A-B have a unique spiro[dienone-tetrahydrofuran] molecular core. These spiro[dienone-tetrahydrofuran] lignans showed comparable neuroprotective effects as the positive control in the H2 O2 -induced SH-SY5Y cells model. In addition, (−)-(7 R, 8 S, 1 ′R, 7 ′R, 8 ′R )-isatispironeol A possessed more significant AChE inhibitory activity, further interact sites were also predicted by the in silico assay. Graphical abstract: Nine tetrahydrofuran lignans, including three undescribed spiro-lignans, were isolated from Isatis indigotica Fortune (Brassicaceae). These undescribed spiro-lignans with a unique spiro[dienone-tetrahydrofuran] molecular core. Image 1 Highlights: Three undescribed spiro-lignans were isolated from Isatis indigotica Fortune. The structure elucidation was achieved by quantum chemical calculation. Isatispironeols A-B have a unique spiro[dienone-tetrahydrofuran] molecular core. These spiro-lignans showed comparable neuroprotective effects. (−)-isatispironeol A possessed greater AChE inhibitory activity.